Pengaruh Media Pembelajaran Augmented Reality Berbasis Marker Based Trancking Dengan Androit dan Motivasi Belajar Terhadap Hasil Belajar Materi Bangun Ruang Pada Siswa Kelas VIII SMP Negeri 1 Bangkalan - Rachmawati, R.Ayu Sari; Wahyuningtyas, Sri; Sunardjo, Sunardjo (Penerbit STKIP PGRI Bangkalan, 2024)
Based on observations at SMPN 1 Bangkalan, it was found that the teacher had not utilized augmented reality-based learning media as a delivery method for material in class and the results of observations indicated that the learning outcomes of mathematics subjects were less than optimal. One potential solution to the aforementioned issues is the implementation of an effective learning model, namely Augmented Reality (AR) learning media. The objective of this study is to examine the interaction effect between the utilization of marker-based tracking-based AR media and learning motivation on the learning outcomes of spatial buildings material in class VIII students at SMP Negeri 1 Bangkalan. The approach employed in this study is quantitative and the research design is experimental. Based on the results of the analysis, it can be seen that the Fcount value = 6,423 with a significance (Sig.) of 0.014. Meanwhile, to test the proposed hypothesis, it is accepted or rejected by looking at the F value and significance (Sig.). the conditions for acceptance or rejection occur if the value of Fcount > Ftable and Significance (Sig.) < 0.05 (Alpha) then H0 is rejected and Ha is accepted. From the output it can be seen that the significance value (asymp sig.) is 0.016. Because the significance value is <0.05, Ho is rejected. So, it can be interpreted that there is an interactive influence between the use of Augmented Reality learning media based on Marker Based Tracking with Android and learning motivation on mathematics learning outcomes.